Linking short-term to long-term convergent tectonics using geodetic observations, geological constraints and numerical simulations - Mallick, Rishav (Nanyang Technological University, 2021)
Earthquakes are the typical association drawn between faults and society. However, faults are not just sources of disaster. They are major contributors to the processes that shape our landscape and climate, since they build geologic structure such as mountain ranges and sedimentary basins. In this dissertation I aimed to gain a comprehensive understanding of faults, from their contributions to seismic hazard and risk to their role as agents of plate tectonics. To understand how faults accumulate elastic strain in the period of time in between earthquakes, I used a newly installed network of GNSS stations from the eastern edge of the India-Eurasia convergent boundary and quantified the slip rates of major faults in the region. However, faults do not only accumulate strain steadily in time. I interpreted sea level records from coral microatolls in terms of tectonic deformation to discover a 32-year Slow-Slip-Event on the Sunda megathrust, offshore Sumatra. This indicates that the period in between earthquakes can be complex and unsteady, and the physics governing this behaviour may sometimes be unexpected. Moving to longer timescales, I tried to bridge earthquake cycle observations (over years) with geological observations of mountain building (over million years). I present a case study of the growth of the Shillong Plateau, north eastern India, as seen in the present-day GNSS-derived velocity field and the long-term uplift history of the plateau. To understand how sequences of earthquakes and aseismic slip on faults shape topography and build mountains, I developed a numerical technique that allows for a one-way coupling from long-term geodynamics to earthquake sequence simulations. This model can be used to make predictions of signals that exist in seismic and geodetic data to help us bridge timescales of deformation. Over the past few decades, we have made significant progress in inferring the geometry and kinematics of fault systems at convergent margins, but continue to be severely limited when it comes to elucidating their dynamics. If we are to make progress in building predictive models, we need to know the underlying mechanics of these systems, and that is the goal for the future.